2016
DOI: 10.4314/sajas.v46i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Production performance of pigs reared in different systems and fed increased energy content diets with or without green alfalfa

Abstract: The objective of this study was to determine the effects of various feeding and housing systems on fattening performance, slaughter value and biochemical serum parameters in growing-finishing pigs. The experimental material comprised 90 growing-finishing pigs, divided into six groups of 15 animals that were diverse in terms of rearing (with or without free access to outdoor runs) and feeding systems (fed increased metabolizable energy (ME) content diets with or without green alfalfa). Different feeding regimes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…In the present study, the average daily body weight gain was 1055 and 970 g/day for indoor and outdoor animals, respectively (P < 0.05, data not shown). Those values are higher than those of Kozera et al (2016), Karpiesiuk and Falkowski (2008) and Hoffman et al (2003), who have reported 740, 727 and 725 g/day, respectively. The genetic characteristics of pigs are most likely responsible for the wide range of daily gains in body weight.…”
Section: Animal Performance and Body Composition Parametersmentioning
confidence: 51%
See 1 more Smart Citation
“…In the present study, the average daily body weight gain was 1055 and 970 g/day for indoor and outdoor animals, respectively (P < 0.05, data not shown). Those values are higher than those of Kozera et al (2016), Karpiesiuk and Falkowski (2008) and Hoffman et al (2003), who have reported 740, 727 and 725 g/day, respectively. The genetic characteristics of pigs are most likely responsible for the wide range of daily gains in body weight.…”
Section: Animal Performance and Body Composition Parametersmentioning
confidence: 51%
“…From our perspective, less feed waste is not firmly possible, especially while the diet was fed ad libitum. Kozera et al (2016) reported no significant difference when pigs were kept indoors with and without free access to outdoor runs. In our design, animals were fully kept in the outdoor system during the entire study period, in which we expect more physical activity (more standing than lying down), postulating high nutritional requirements.…”
Section: Animal Performance and Body Composition Parametersmentioning
confidence: 96%
“…The direction and significance of the effect of housing conditions on the growth and slaughter performance of pig fatteners are inconsistent. Some studies have reported that the housing system does not have an impact on most of the traits related to fattening performance and slaughter value [ 71 ]. On the other hand, some have concluded that the housing system influences only some characteristics of fattening performance [ 72 ], while some have pointed out the relationship between the housing system and performance of pig fatteners [ 24 , 73 ].…”
Section: Effect Of On-farm Environment On the Welfare Of Growing Pigs And Fattenersmentioning
confidence: 99%
“…Juska et al [ 72 ], in their study conducted in Lithuania, compared pigs reared indoors with those reared outdoors and found that outdoor-raised pigs were characterized by a higher daily gain in the growing and growing-finishing period, and a higher final weight in the growing and finishing period. Kozera et al [ 71 ] compared fatteners from mating (Polish Large White × Polish Landrace) sows with (Duroc × Pietrain) boars kept indoors and outdoors with access to outdoor runs and noted that, under the Polish climatic conditions, the housing system did not affect the fattening performance and slaughter traits of those crossbreds. Acciaioli et al [ 73 ] analyzed the influence of the housing system on the performance of Cinta Senese (CS), commercial Large White (LW), and their crossbreds (LW × CS) by assigning the animals to outdoor and indoor systems, under the climatic conditions of Italy.…”
Section: Effect Of On-farm Environment On the Welfare Of Growing Pigs And Fattenersmentioning
confidence: 99%
“…The exorbitant price and marked shift in availability of conventional feed ingredients particularly dietary energy source for the pig industry (Kozera et al, 2016) implied exploring a wider range of alternative feedstuffs in formulating diets for pigs. Cassava and its products have received attention from swine nutritionist.…”
Section: Introductionmentioning
confidence: 99%